Enhanced Fluorescence Detection of Interleukin 10 by Means of 1D Photonic Crystals - Agostino Occhicone; Paola Del Porto; Norbert Danz; Peter Munzert; Alberto Sinibaldi; Francesco Michelotti (Crystals, 2021)
In the present communication, we report on the exploitation of a Bloch surface wave-enhanced fluorescence scheme for the detection of Interleukin (IL)-10 in a protein-rich buffer mimicking a biological sample. IL-10 is a cytokine known for its potent anti-inflammatory and immunosuppressive effects. It is considered a valuable biomarker for prognostic prediction for both solid tumors and hematological malignancies, and recently, a distinguishing feature of hyperinflammation during severe viral infections. To demonstrate the validity of the technique, we transferred all the reagents and working concentrations used in a gold-standard technique, such as ELISA, to our assay, with a substantial reduction in the execution time and without using any enzymatic amplification during IL-10 recognition. We estimate a limit of detection (LoD) in terms of the concentration of IL-10 in solution of the order of 110 pg/mL (5.8 pM) with a 14% accuracy; in other terms, the presented technique is compatible with the assay range and resolution (1.6 pM) of commercial gold-standard ELISA kits. Moreover, such LoD successfully matches the concentrations reported in literature for IL-10 detection in COVID-19 patients, making the BSW-based sensors a viable solution for rapid and accurate screening of COVID-19-related molecules.